The Use of E- Learning trough Google Classroom to Improve Students’ Articulation Phonetic Ability - Much Deiniatur (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2019)
This study aims to determine whether Google classroom can improve the students’ ability in articulation phonetics or pronunciation at the English Department of IAIN MetroThe type of this research is classroom action research. It was conducted in 2 cycles. Data collection techniques of this study were observation, tests, documentation, interviews, and field notes. The results of this research showed that there was improvement the students’ ability in Articulation Phonetics. It can be seen from the average score in pre test was 60,3, post test cycle 1 was 64, 5, and post test cycle 2 was 75,8.From the results, it can be concluded that the use of google classroom can improve the ability of articulation phonetics at English Department of IAIN Metro.